2015
DOI: 10.14393/bj-v31n4a2015-26218
|View full text |Cite
|
Sign up to set email alerts
|

Least limiting water range and degree of compactness of soils under no- tillage

Abstract: ABSTRACT:The least limiting water range (LLWR) and degree of compactness (DC) can be useful indicators of soil physical quality and crop yield. This study focused on assessing of LLWR, DC and evaluation of critical values to crop growth of an Alfisol and Oxisol under no-till management. Undisturbed soil cores were taken from the layer 0.00 -0.20 m depth. Soil water retention curve, soil penetration resistance curve, air-filled porosity and bulk density (Bd) were measured. The range of LLWR variation was limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
1
0
0
1
Order By: Relevance
“…Regardless of the soil class, the available water content (AWC = θ FC -θ PWP ) was always higher than the LLWR, which characterizes the soils as physically degraded. Due to such behavior, Silva et al (1994) A similar condition of the LLWR variation in the LVd found in the present study was also verified by Lima et al (2015) in an Oxisol Table 4. Soil water retention curve and soil penetration resistance curve for an LVd and an LVef at the layer of 0-0.20 m depth for different agricultural management systems.…”
Section: Resultssupporting
confidence: 88%
“…Regardless of the soil class, the available water content (AWC = θ FC -θ PWP ) was always higher than the LLWR, which characterizes the soils as physically degraded. Due to such behavior, Silva et al (1994) A similar condition of the LLWR variation in the LVd found in the present study was also verified by Lima et al (2015) in an Oxisol Table 4. Soil water retention curve and soil penetration resistance curve for an LVd and an LVef at the layer of 0-0.20 m depth for different agricultural management systems.…”
Section: Resultssupporting
confidence: 88%
“…O Intervalo Hídrico Ótimo (IHO) é definido como sendo o volume de água retido no solo no qual as limitações ao desenvolvimento de plantas associadas à disponibilidade de água, aeração e resistência do solo à penetração são mínimas. O IHO tem se mostrado uma ferramenta útil para avaliar a qualidade estrutural do solo e o impacto das práticas de manejo sobre a produtividade do sistema agrícola (SILVA; KAY; KAY, 1996;KAY, 1997;LIBARDI, 1998;SHARMA;BHUSHAN, 2001;IMHOFF, SILVA E TORMENA, 2000;LEAO, 2002;ARAÚJO;BEUTLER et al, 2004;GUIMARÃES et al, 2013;GUBIANI et al, 2013;GUEDES FILHO;BLANCO-CANQUI;SILVA, 2013;LIMA et al, 2015). Araujo et al (2004) compararam o IHO de um solo sob mata nativa e de um solo cultivado e constataram que no solo cultivado, o aumento da densidade do solo (Ds) condicionou redução do valor do IHO decorrente do efeito simultâneo sobre a porosidade de aeração (PA) e sobre a resistência do solo á penetração (RP).…”
Section: Introductionunclassified